EVALUATION OF THE AESTHETIC RESULT OF A SINGLE DENTAL IMPLANT PROSTHETICS - M.SH. SULTANOV; O.A. SOCHAEV (Avicenna Tajik State Medical University, 2023)
Objective: A comparative assessment of the aesthetic result of a single dental implant (DI) prosthetics using standard or custom abutments. Methods: A customized gingival former and a custom abutment were applied in patients of the main group, while patients of the control group received a standard gingival former and a stock abutment. The aesthetic assessment was carried out on photographs using the Pink Esthetic Score (PES) and White Esthetic Score (WES) scales. Results: Better aesthetic results were obtained in the main group compared to the control one. At subsequent stages of the study, a further aesthetical improvement was observed compared with the initial assessment result. Conclusion: The formation of a marginal gingiva matching the anatomical shape of the neck of the missing tooth enables to fabricate a customized abutment and a dental crown of the correct anatomical shape. The physiological dimensions and the correct eruption profile of the prosthetic crown contribute to the formation of interdental papillae where they were originally absent. The listed advantages of this method improve the RES and PES results of prosthetics on a single-unit DI.